IPTEKS PENGHITUNGAN HARGA TRANSFER DAN HARGA JUAL PADA RUMAH MAKAN KHOPINOS - Budiarso, Novi Swandari; Pontoh, Winston (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2019)
Determination of transfer prices and selling prices is not only a matter of large companies. This problem can occur in a type of Small and medium enterprise. But sometimes managers from small and medium businesses do not realize that in their business there is a transfer price transaction that can affect the selling price of the product to external consumers and subsequently affect operating profit. In order to overcome this problem, you can use the transfer pricing method and selling price so that you get the right transfer price and selling price for a business. The results of the transfer price calculation using the cost method and the selling price using the full cost method, the results of the transfer of semi-finished products from the preparation business unit are Rp. 4,900 / unit, while the selling price of the settlement division to external consumers is Rp. 11,020 / unit .